Broader Impacts for Ecologists: Biological Soil Crust as a Model System for Education - Faist, Akasha M.; Antoninka, Anita J.; Barger, Nichole N.; Bowker, Matthew A.; Chaudhary, V. Bala; Havrilla, Caroline A.; Huber-Sannwald, Elisabeth; Reed, Sasha C.; Weber, Bettina (Frontiers in Microbiology, 2021)
Biological soil crusts (biocrusts) are a complex community of algae, cyanobacteria, lichens, bryophytes, and assorted bacteria and fungi that colonize the soil surface. Biocrusts are particularly common in drylands and are found in arid and semiarid ecosystems worldwide. While diminutive in size, biocrusts often cover large terrestrial areas, provide numerous ecosystem benefits, enhance biodiversity, and are found in multiple configurations and assemblages across different climate and disturbance regimes. Biocrusts have been a focus of many ecologists, especially those working in semiarid and arid lands, as biocrusts are foundational community members, play fundamental roles in ecosystem processes, and offer rare opportunities to study biological interactions at small and large spatial scales. Due to these same characteristics, biocrusts have the potential to serve as an excellent teaching tool. The purpose of this paper is to demonstrate the utility of biocrust communities as a model system in science education. Functioning as portable, dynamic mini ecosystems, biocrusts can be used to teach about organisms, biodiversity, biotic interactions, abiotic controls, ecosystem processes, and even global change, and can be easy to use in nearly every classroom setup. For example, education principles, such as evolution and adaptation to stress, or structure and function (patterns and processes) can be applied by bringing biocrusts into the classroom as a teaching tool. In addition to demonstrating the utility of biocrusts in the classroom - including theory, hypothesis testing, experimentation, and hands-on learning - this document provides tips and resources for developing education tools and activities geared toward impactful learning.